GOOD CORPORATE GOVERNANCE IN NON-FINANCIAL SECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Lukito, Excel Nathaniel; Murhadi, Werner R; Wijaya, Liliana Inggrit (Universitas Pakuan, 2024)
ABSTRACTThe purpose of this study is to look at how good corporate governance affects the financial performance of all companies in the non-financial sector that are listed on the Indonesia Stock Exchange. This study employs a sample of non-financial companies listed on the Indonesia Stock Exchange and the ordinary least squares approach with panel data. The study's findings show that the board of commissioners' independence variable has a positive impact on ROA and TOBIN's Q; board size has a negative impact on ROA and a positive impact on TOBIN'S Q; the audit committee has a negative impact on ROA and TOBIN'S Q; institutional ownership has a positive impact on ROA and Tobin's Q; organizational size has a positive impact on ROA and a negative impact on TOBIN'S Q; and leverage has a negative impact on both ROA and TOBIN'S Q. According to this research, businesspeople should be aware that there are independent commissioners who can send out encouraging signals to potential investors. However, the audit committee has not been successful in sending investors a negative message.ABSTRAKTujuan dari penelitian ini adalah untuk melihat bagaimana pengaruh tata kelola perusahaan yang baik terhadap kinerja keuangan pada seluruh perusahaan di sektor non-keuangan yang terdaftar di Bursa Efek Indonesia. Penelitian ini menggunakan metode ordinary least square dengan data panel dan menggunakan sampel perusahaan non-keuangan yang terdaftar di Bursa Efek Indonesia. Hasil penelitian ini menunjukkan bahwa variabel independensi dewan komisaris memiliki pengaruh positif terhadap ROA dan terhadap TOBIN'S Q, ukuran dewan memiliki pengaruh negatif terhadap ROA dan positif terhadap TOBIN'S Q, komite audit memiliki pengaruh negatif terhadap ROA dan TOBIN'S Q, kepemilikan institusional berpengaruh positif terhadap ROA dan Tobin's Q, ukuran perusahaan berpengaruh positif terhadap ROA dan berpengaruh negatif terhadap TOBIN'S Q dan leverage berpengaruh negatif terhadap ROA dan TOBIN'S Q. Implikasi dari penelitian ini adalah pelaku bisnis diharapkan memperhatikan keberadaan komisaris independen yang mampu memberikan sinyal positif bagi investor. Sebaliknya, komite audit belum efektif memberikan sinyal negatif bagi investor.